Fantasy architects an inside look at the Dragon Age: origins toolset. - Desslock
BioWare recently flew in select members of its Dargon Age and Neverswinter NIghts communities to get under the hood of its extensive campaign creation toolset ahead of release. PC Gamer was on hand to capture the details.
Keywords: Dragon Age; Video games; Role playing games